The Influence of the Discovery Learning Model Assisted by Kahoot Media on Learning Outcomes - Karmina, Putri; Dewi, Ratna Sari (Universitas Negeri Medan, 2025)
This study examined the effect of the Discovery Learning model assisted by Kahoot media on students' activities and learning outcomes on the topic of atomic structure. This study involved students of class X IPA SMA IT Jabal Noor Medan, with purposive sampling selecting class X PSP B as the experimental class (Discovery Learning with Kahoot) and class X PSP A as the control class (conventional learning). The test and non-test instruments used were valid, and the data met the assumptions of normality and homogeneity. The results showed that the experimental class achieved a higher average activity score (87.6) than the control class (76), with a significant difference (t count = 6.305 > t table = 2.023). The N-Gain score of the experimental class (0.83) also exceeded the N-Gain score of the control class (0.75). These findings indicate that the Discovery Learning model assisted by Kahoot is effective in increasing students' activities and learning outcomes in studying atomic structure.